Vacancies in sulfides facilitate fluid-induced solid-state diffusion and critical metals accumulation - Zheng-Jie Qiu; Yanlu Xing; Joël Brugger; Barbara Etschmann; Zsanett Pintér; Denis Fougerouse; Jing Xu; Zhiyang Yu; Guang-Jun Guo; Hong-Rui Fan (Nature Communications)
Abstract Understanding elements uptake and release from minerals in source rocks is crucial for comprehending critical metals accumulation, yet the mechanisms and kinetics of element mobilization at the atomic scale remain mostly unknown. Here, we analyzed the distribution of cobalt (Co) in natural pyrite from a Cu-Co ore deposit and found that metals distribution is best described by steady-state diffusion with constant flux and concentration-dependent diffusivities, rather than transient-state diffusion with time-evolving concentrations. First-principles calculations and diffusion modelling further demonstrate that this diffusion is accelerated by vacancy pathways and is far more efficient than traditional vacancy-mediated lattice diffusion, with element transfer rates higher by almost two orders of magnitude. We conclude that steady-state lattice diffusion induced by vacancies in the presence of fluid can be an efficient mechanism promoting the preferential release of metals into ore fluids and the accumulation of metals during ore formation.